2009
DOI: 10.1534/genetics.108.099846
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin-Mediated Association of Achiasmate Homologs Declines With Age When Cohesion Is Compromised

Abstract: Normally, meiotic crossovers in conjunction with sister-chromatid cohesion establish a physical connection between homologs that is required for their accurate segregation during the first meiotic division. However, in some organisms an alternative mechanism ensures the proper segregation of bivalents that fail to recombine. In Drosophila oocytes, accurate segregation of achiasmate homologs depends on pairing that is mediated by their centromere-proximal heterochromatin. Our previous work uncovered an unexpect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…Similar observations have been reported for solo male meiosis and ord male and female meiosis [51][53], [60], [61], [73] and indicate the existence of centromere cohesion that is independent of both SOLO and ORD and perhaps of cohesin (although the possible presence of low levels of cohesin near centromeres in solo and ord mutants cannot be ruled out). Whether this early prophase cohesion is based on a protein complex or on chromatid entanglement remains to be determined.…”
Section: Discussionsupporting
confidence: 84%
“…Similar observations have been reported for solo male meiosis and ord male and female meiosis [51][53], [60], [61], [73] and indicate the existence of centromere cohesion that is independent of both SOLO and ORD and perhaps of cohesin (although the possible presence of low levels of cohesin near centromeres in solo and ord mutants cannot be ruled out). Whether this early prophase cohesion is based on a protein complex or on chromatid entanglement remains to be determined.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, FM7a/X homologs rely entirely on the achiasmate system for accurate segregation. We have previously shown that because centromere proximal heterochromatin on FM7a is greatly reduced, the FM7a/X pair provides a sensitized system to investigate the mechanisms underlying PHeMAAH (Subramanian and Bickel 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This means that weakened PHeMAAH between a pair of homologs during prophase I does not always result in missegregation during anaphase I. Our previous work has shown that a reduction of pericentric heterochromatin on one of the chromosomes of an achiasmate X chromosome pair sensitizes it to missegregation under conditions that perturb PHeMAAH (Subramanian and Bickel 2009). This is the case for the FM7a/X achiasmate chromosome pair that we have used in our analyses.…”
Section: Weakened Phemaah Predisposes Achiasmate Homologs To Segregatmentioning
confidence: 96%
“…As such the present report of the presence of achiasmate meiosis coupled with inter-telomeric connections is the first report for T. spathacea. While inter chromosomal connections have been attributed mostly to fixation artifact [33] and to the fusion of heterochromatic region between the chromosomes [16,39,62,65], achiasmate meiosis has been assigned to the presence of mutant gene(s) affecting chiasmata formation [2,21,32,34,60], alteration in temperature/humidity [34,60,67], defective synaptonemal complex formation [14,21,24,60] and to disturbed supply of potassium and phosphate ions to the tissue [2,60]. In the present material inter-telomeric connections cannot be attributed to any of the two factors mentioned elsewhere on account of the fact that this feature was discerned only in some buds while other buds showed meiotic features characteristic of complex translocation heterozygote and supported the earlier reports [17,18,31,36,37,41,42,55,56,64].…”
Section: Discussionmentioning
confidence: 99%